Logistical challenges in family farming production in DomPedrito – RS, Brazil: a multiple case study - Maia, Joélio Farias (2019)
This work is part of a more extensive study on the management of family farming activities in the municipality of Dom Pedrito-RS and aimed to discuss the challenges of logistics in the distribution of production from family farming, linked to participating farmers of Feira Livre de Dom Pedrito. To achieve the objectives of this work, a qualitative research was conducted through interviews with participatory observation in a multiple case study, performed in the first semester of 2018 and interpreted through textual discourse analysis. Sixteen family farmers with one main factor in common participated in this study: they commercialized their products at the Feira Livre de Dom Pedrito. In this location, through interviews, the main challenges faced by these farmers to market their products were pointed out. The main results highlight the deficiency in the road infrastructure connecting the interior of the municipality to the place of sale. That is, from the property to the fair held in the city center, mainly taking into account climatic factors such as rain and flooding. Logistics problems cause difficulties for Dom Pedrito family farmers. Some groups feel better infrastructure conditions and can maintain their production and marketing activities at the Fair. However, for other farmers, the problems faced as poor road conditions, lack of maintenance are serious on roads, lack of paving and weather factors. These conditions interfere with the aspect related to the Fair, sometimes preventing farmers to make their sales, resulting in loss of production, increased costs and decreased family income.